ANALISIS PERBANDINGAN EKUITAS MEREKKARTU SELULER MEREK SIMPATIDAN XL PRABAYAR: THE COMPARATIVE ANALYSIS OF BRAND EQUITY OF SIMPATI SIMCARD AND PREPAID XL SIMCARD - Masria Naingolan (DIGEST MARKETING, 2018)
This research purpose is to explain attributes differences of two simcards: 1) simPATI and 2) Xl prepaid category product. The diferences relate with brand equity (brand awarenss, brand associations, brand perceived quality and brand loyalty) on each simcard resepectively. Survey used onlinequestionnaire that deliver directly to the respondents. Analysis methode used is Mann-Whitney test. Based on this research, it is found that the difference between brand equity simPATI and XL Prabayar. The score for prepaid XL brand equity is higher than simPATI. Brand equity elements are perceived quality and brand loyalty indicated the differentiation significantly, while brand awereness and brand association has no significant different. Keywords: brand association, brand awereness, brand equity, brand loyal, perceived quality